Lower extremity arterial calcifications assessed by multislice CT as a correlate to coronary artery disease - Gamal Samir Gamal Aly; Hussien Heshmat Kassem; Assem Hashad; Mohammad Ali Salem; Dina Labib; Essam Baligh (The Egyptian Journal of Radiology and Nuclear Medicine, 2020)
Abstract Background Patients with peripheral artery disease (PAD) frequently have concomitant coronary artery disease (CAD) and display a higher risk for myocardial infarction, stroke, and death due to cardiovascular events. In order to prevent cardiovascular events, there is an increasing interest in new markers of atherosclerosis. Vascular calcifications (VC) are often present in the early stages of atherogenesis and could be considered an early marker. The aim of this study is to correlate the extent of lower limbs, aortic, and coronary arterial calcification diagnosed by non-contrast multislice CT with the severity of coronary artery disease diagnosed by conventional coronary angiography. Results There is borderline significant association between CAD (Gensini score) and each of total lower limb and aorto-iliac calcifications. There is significant association between the number of diseased coronaries and lower limb calcifications. Also, there is significant association between the coronary artery calcifications and lower limb arterial calcifications (total and segmental). Diabetes mellitus and hypertension are significantly associated with lower limb calcification (total, aorto-iliac, and infra-popliteal). Moreover, lower limb arterial calcifications (total and segmental) are positively correlated with increasing age. Conclusion Lower limb arterial calcifications, as diagnosed by non-contrast MSCT, is a noninvasive measure for evaluation of the atherosclerotic burden that correlate to the CAD; it can aid to refine risk stratification and the need for more aggressive preventive strategies.